Pengaruh Latihan Range of Motion (ROM) Aktif Terhadap Peningkatan Kekuatan Otot Ekstremitas Bawah Lansia - Suwito, Adriani; Sary, Nurfatma (REAL in Nursing Journal, 2019)
Musculoskeletal system disorders of weakness in the muscles of the elderly are common. Actions that can be taken to reduce complaints of the elderly are with range of motion (ROM) exercises. The purpose of this study was to determine the effect of active range of motion (ROM) exercises on increasing the strength of lower limb muscles in the elderly. Pre-experimental research design with one group pre-test and post-test. By means of purposive sampling with 6 respondents. Giving intervention as much as 6 times exercise for 3 weeks with a frequency of 2 times a day . It takes 10 minutes with 3 repetitions of movements. Analysis was performed by paired dependent T-test samples. The results showed that the average lower limb muscle strength in the elderly before active ROM exercises were the hip region = 3.03317, the knee region = 3.44433, the ankle region = 3.24300, the toe region = 3.31950. While the average lower limb muscle strength after active ROM exercises are the hip region = 3.22117, knee region = 3.76367, ankle region = 3.51383, toe area = 3.86800, with hip value p = 0.028, knee p = 0.002, ankle p = 0.002, toe p = 0,000. Based on the results of the study it can be concluded that there is an effect of active range of motion (ROM) exercises on increasing muscle strength in the elderly. This research is expected to be a consideration for the elderly orphanages in order to make the range of motion (ROM) as an exercise program to increase muscle strength in the elderly.